Derivation and Functional Analysis of Patient-Specific Induced Pluripotent Stem Cells as an In Vitro Model of Chronic Granulomatous Disease - Jiang, Yan (Wiley Subscription Services, Inc., A Wiley Company, 2012)
Chronic granulomatous disease (CGD) is an inherited disorder of phagocytes in which NADPH oxidase is defective in generating reactive oxygen species. In this study, we reprogrammed three normal unrelated patient's fibroblasts (p47(phox) and gp91(phox)) to pluripotency by lentiviral transduction with defined pluripotency factors. These induced pluripotent stem cells (iPSC) share the morphological features of human embryonic stem cells, express the key pluripotency factors, and possess high telomerase activity. Furthermore, all the iPSC lines formed embryoid bodies in vitro containing cells originating from all three germ layers and were capable of teratoma formation in vivo. They were isogenic with the original patient fibroblasts, exhibited normal karyotype, and retained the p47(phox) or gp91(pho)(x) mutations found in the patient fibroblasts. We further demonstrated that these iPSC could be differentiated into monocytes and macrophages with a similar cytokine profile to blood-derived macrophages under resting conditions. Most importantly, CGD-patient-specific iPSC-derived macrophages showed normal phagocytic properties but lacked reactive oxygen species production, which correlates with clinical diagnosis of CGD in the patients. Together these results suggest that CGD-patient-specific iPSC lines represent an important tool for modeling CGD disease phenotypes, screening candidate drugs, and the development of gene therapy. Stem Cells 2012; 30:599–611